Initial Conditions and Resilience in the Atmospheric Boundary Layer of an Urban Basin - Patricio Pacheco; Eduardo Mera; Voltaire Fuentes; Carolina Parodi (Atmosphere, 2023)
The possibilities of micrometeorological resilience in urban contexts immersed in a basin geographical configuration are investigated. For this purpose, time series data with measurements of meteorological variables (temperature, magnitude of wind speed and relative humidity) and atmospheric pollutants (PM2.5, PM10, CO) are analyzed through chaos theory, calculating the coefficient of Lyapunov (λ), the correlation dimension (Dc), the Hurst coefficient (H), the correlation entropy (SK), the fractal dimension (D) and the Lempel–Ziv complexity (LZ). Indicators are built for each measurement period (2010–2013 and 2017–2020), for each locality studied and located at different heights. These indicators, which correspond to the quotient between the entropy resulting from the meteorological variables and that of the pollutants, show sensitivity to height. Another important indicator, for identical measurement conditions, arises from the calculation of the fractal dimensions of the meteorological variables and that of the pollutants, which allows for comparative studies between the two periods. These indicators are conclusive in pointing out that, in a large city with basin geographical characteristics, subjected to an intensive urbanization process, there is no micrometeorological resilience and a great variation occurs in the initial conditions.